Renewable Energy on Islands: Lessons for Indonesia to Apply - Rianto, Faizal; Utari, Diah Siti; Jenawi, Billy; Sujarwani, Riau (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2020)
The purpose of this article is to examine lessons and examples from renewable energy initiatives implemented on islands and archipelagos to drive its use in Indonesia. Indonesia has achieved 91.16% electrification ratio in 2016, and in 2024 planned to achieve electrification ratio of 100%. Lack of electricity access, however, is endemic throughout Indonesia. Due to its geography, providing electricity to Indonesia’s population is a daunting task as its archipelagic landscape poses a challenge in electrification efforts. Studies and case studies have shown the potential application of renewable energy on islands as small islands can make the transition to renewable energy. Due to the importance in providing electricity to small populated islands to achieve higher electrification ratio, it is therefore important for Indonesia to take note that renewable energy initiatives, particularly on islands, are not only yielding positive results socially, economically, and environmentally, but it is also viable and feasible to implement